Minimal age-related variation in bipedal behavior in Sapajus - Kristin A. Wright; Dorothy M. Fragaszy (Revue de Primatologie)
Our understanding of how bipedalism evolved in hominins has been refined through studies of bipedal behavior in non-human primates, both in the wild and in the laboratory. Bipedal behavior in non-human primates makes up a relatively small portion of their behavioral repertoire. Understanding when bipedal behaviors occur and how bipedal behaviors emerge can provide further insight into the context in which bipedal behaviors may have evolved. Here, we examine age-related variation in bipedal behavior in wild bearded capuchins (Sapajus libidinosus). 2,209 records of bipedal posture and locomotion, activity state, and substrate used during bipedal behavior (17.2% of all records of positional behavior) were examined for individuals ranging from 3 months to 15 years or older in two groups (32 individuals in total). Apart from very young individuals that were carried by older conspecifics, individuals of all ages showed similar rates and patterns of bipedal behaviors. Bipedal postures were used predominantly during feeding and foraging, most often in arboreal settings, and most often with their prehensile tail grasping, or in contact with, the substrate. Bipedal locomotion occurred most often on terrestrial substrates and comprised only 3% of all records of bipedal behavior.